Desenvolvimento das árvores em áreas de preservação permanente de mananciais reflorestadas por jovens florestais em Jaboticabal-SP - Silva, Ebson [UNESP] (2015)
This work is part of university extension project entitled "Young forest: the seed in your hands", which aims to develop and teach basic techniques of seedling production, reforestation and environmental education, having as target elementary school students, apprentices with special needs belonging to the Association of Parents and Friends of Exceptional Children - APAE Taiaçu-SP and Association of Parents and Friends of the Deaf and Dumb - APAS Jaboticabal-SP. It aims to evaluate the growth rate of planted tree species in an area of permanent preservation around the spring of the São Paulo State University, College of Agriculture, Campus of Jaboticabal -SP and the effectiveness of reforestation. The reforestation was held on 17-02- 2011 by elementary school students and apprentices of APAE, who assisted in planting 506 seedlings of 80 native species of different successional ecological groups: pioneer, secondary and climax in an area of 2,277 m2 to around the spring. Evaluations were made of height, stem diameter (DAP) and mean annual increment (MAI) of these characteristics of plants to 2.5 and 4.5 years old. The rate of growth in height and stem diameter was higher in the group of pioneer species, intermediate in the group of secondary and inferior species in the group of climax species. It was observed an increase of the growth rate of plants during the period of 4.5 years of evaluation for the three groups of species. It is concluded that the reforestation techniques used were effective.